HPJA special edition introductory comments - Andrew Wilson; Sonia Wutzke (Health Promotion Journal of Australia, 2018)
Issue addressed Their position as a target demographic of the tobacco industry means younger people are best placed to provide information on the activities of industry actors in relation to nicotine pouches. Accordingly, we aimed to qualitatively examine younger people's exposure to pouch advertising, from where pouches are being sourced, and any notable retailer practices and industry innovations. Methods Australians aged 16-39 years were recruited to participate in one of 12 focus groups held February to April 2025. Groups ranged in size from 6 to 10 participants, with a total of 98 participants in attendance. Data were synthesised using template analysis. Results Almost all groups reported being exposed to nicotine pouch advertising, despite such advertising being illegal in Australia. Social media was the most common source of advertising exposure, with TikTok the most frequently cited platform. Participants reported that advertising typically featured attractive influencers portraying pouches as "cool" and describing nicotine as "natural". Tobacconists and convenience stores were key product sources. Few retailer practices were identified, with these broadly relating to product cost and inducements. Conclusions Results provide initial insights into the insidiousness of the marketing strategies being adopted to sell nicotine pouches to younger people. SO WHAT?: Findings highlight an urgent need for action that protects younger people from tobacco companies and the influencers they engage to promote their addictive products. Action should include robust regulation of the online environment and holding social media platforms responsible for their failure to enforce policies prohibiting product advertising and sales.